Transoral laser microsurgery for the unknown primary: Role for lingual tonsillectomy - Nagel, Thomas H.; Hinni, Michael L.; Hayden, Richard E.; Lott, David G. (Head & neck, 2014)
Background We conducted a retrospective review of patients with unknown primary head and neck cancer who underwent a transoral laser microsurgery (TLM)‐assisted search for an occult tumor. Methods Fifty‐two patients at a single center with unknown primaries of squamous cell carcinoma (SCC) were treated with a surgical algorithm. Results The overall rate of primary tumor identification was 75% (39 of 52 patients). When selecting those cases in which a TLM algorithm with lingual tonsillectomy was utilized, the detection rate was 86% (31 of 36). Tumors were most commonly found in the lingual (65.0%) and palatine tonsils (27.5%). When directed biopsies did not locate a tumor, a higher yield was obtained with the addition of a lingual tonsillectomy in 8 patients. Conclusion A surgical algorithm for the unknown primary that includes TLM‐assisted techniques, including a lingual tonsillectomy, offers the greatest likelihood of successfully detecting the location of occult primary tumors. © 2014 Wiley Periodicals, Inc. Head Neck 36: 942–946, 2014